Fashion and contemporaneity : realms of the visible - Petican, Laura, 1972- (At the interface/probing the boundaries ;, 2019)
This book represents the voices of scholars, fashion designers, bloggers and artists, who speak to the pervasive nature of fashion in matters of politics, history, economics, sociology, religion, culture, art and identity. Dialogically open, the volume offers a broad apprehension of visual matter in the global contemporary context with fashion at its core, exploring its metamorphosing, media-oriented and 'disordered' modes of being in the early twenty-first century. The book's contributors consider topics of universal import stemming from the realm of fashion, its dissemination and impact, from institutional, corporate, collective and individual perspectives, reflecting on the morphing, interchanging and revolutionary quality of the visual realm as the basis for continued research in fashion studies. Contributors are Shari Tamar Akal, Jess Berry, Naomi Braithwaite, Claire Eldred, Sarah Heaton, Hilde Heim, Demetra Kolakis, Sarah Mole, Lynn S. Neal, Laura Petican, Cecilia Winterhalter, Manrutt Wongkaew.